THE MAIN CHALLENGES AND STRATEGIES FOR ADAPTING THE TRANSPORT AND LOGISTICS SYSTEM DURING MARTIAL LAW - Sukhetska, Kristina (Current Problems of Sustainable Development, 2026)
The article presents a comprehensive analysis of the main obstacles to the functioning of Ukraine’s transport and logistics system (TLS) under martial law and summarises the directions of its adaptation. Drawing on official data from the KSE Institute, the joint Rapid Damage and Needs Assessment by the World Bank, UN and European Commission, statistics from the Ministry for Communities and Territories Development, the State Statistics Service of Ukraine and JSC «Ukrzaliznytsia», a set of destructive factors is identified: direct destruction of infrastructure assets, targeted missile and drone strikes on critical nodes, the loss of direct access to some sea ports and the Azov coastline, complications of westbound transit caused by blockades, labour shortages, energy constraints and rising operational costs. The paper systematises adaptation tools: the Ukrainian maritime corridor, the EU «Solidarity Lanes» initiative, deployment of the European-gauge railway, multimodal routes (including the Trans-Caspian one), digitalisation of logistics processes and diversification of logistics hubs. A conceptual approach to enhancing the resilience of Ukraine’s TLS based on redundancy, diversification, integration into the TEN-T network and deep digitalisation is proposed.
Keywords: transport and logistics system; critical infrastructure; logistics resilience; management; digitalisation; transport logistics; business competitiveness